2020
DOI: 10.1111/beer.12294
|View full text |Cite
|
Sign up to set email alerts
|

CSR and banking soundness: A causal perspective

Abstract: This is the first study to examine the relationship between sustainability and soundness in banking as part of an integrated reporting approach. We consider 12 major European banks over the period 2006–2016. To test the relationship, two indexes were constructed, the sustainable performance index, which attempts to measure sustainability, and the banking soundness index, which measures bank soundness. The results show a bidirectional causality between sustainability and banking soundness. More specifically, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 79 publications
(107 reference statements)
0
9
0
Order By: Relevance
“…In particular, since stakeholder engagement in sustainable development pushes banks to behave ethically and responsibly (ben Abdallah et al, 2020; Galletta, Mazzù, Naciti, et al, 2021; Khattak & Saiti, 2021; Raut et al, 2017; Scholtens, 2009), banks' compliance with ESG criteria should match their actions against commitments to reduce ESG controversies. Therefore, if a scandal occurs, the bank involved is penalized, and this affects its overall ESG score and grading.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, since stakeholder engagement in sustainable development pushes banks to behave ethically and responsibly (ben Abdallah et al, 2020; Galletta, Mazzù, Naciti, et al, 2021; Khattak & Saiti, 2021; Raut et al, 2017; Scholtens, 2009), banks' compliance with ESG criteria should match their actions against commitments to reduce ESG controversies. Therefore, if a scandal occurs, the bank involved is penalized, and this affects its overall ESG score and grading.…”
Section: Introductionmentioning
confidence: 99%
“…They found that discretionary accrual management overestimates the company, causing its stock prices to rise. The study [8] mentions the topic of earnings management in connection with the analysis of the relationship between sustainability and reliability in banking. In the study [9], the authors deal with the influence of the result of earnings management from the point of view of the interest of shareholders towards the interests of the company's managers and also the methods of earnings management on the credibility of the company for shareholders.…”
Section: Reviewmentioning
confidence: 99%
“…Sustainability points are customer satisfaction, good profitability, superior performance in the medium and long-term, and a contribution to the whole financial system by controlling and monitoring risk levels. 14 In contrast to the current developing theory, implementing sustainability is by implementing CSR. According to Shariah principles, the CSR concept is more than wanting to get a positive image and long-term impact but rather to the dimensions of service to God, environment and society.…”
Section: A Introductionmentioning
confidence: 99%